Ferenc Kozár – A dedicated and prolific worker on scale insects - Williams, D.J.; Kaydan, M.B. (ENTOMOLOGIA HELLENICA, 2010)
At the XII Meeting of the International Symposium on Scale Insect Studies, delegates and coccidologists worldwide congratulate Dr Ferenc Kozár for his work on scale insects during over 40 years of concentrated study. Ferenc is well known for his contributions to economic and taxonomic work on scale insects. He entered the Agricultural University in Budapest, Hungary, in 1962, and then the University of Leningrad (now St Petersburg) and returned to Hungary where he has been employed as Research Scientist and then Head of the Department of Zoology of the Hungarian Academy of Sciences in Budapest until 1990. He then became Research Consultant, a position he has held since. His list of publications includes nine books and about 220 papers in scientific journals. He has described 13 new family-group names, 32 new genera, and about 175 new species. Much of this work has been done since 1990. We expect a steady flow of publications in the future.